1998
DOI: 10.1046/j.1464-410x.1998.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Epididymectomy in the management of intrascrotal disease:

Abstract: Objective  To assess the outcome of epididymectomy as a method of treating epididymal pathology. Patients and methods  Forty‐one patients who underwent epididymectomy between 1990 and 1995 were analysed retrospectively; their clinical records were reviewed and their satisfaction with the outcome and relief of symptoms assessed using a questionnaire and/or telephone interview. Results  Twenty‐nine patients with pain were subdivided into three categories depending on the indication for epididymectomy, i.e. post‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Siu et al 21 likewise claimed 100% patient satisfaction in 25 patients with PVPS undergoing epididymectomy. Furthermore, Sweeney et al 22 reported a satisfaction level of 87.5% with this technique, recording best overall outcomes in the PVPS group, while Chen and Ball 23 indicated that 5 of 10 patients with PVPS (50%) were pain-free after epididymectomy. In spite of these successes, epididymectomy with PVPS remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Siu et al 21 likewise claimed 100% patient satisfaction in 25 patients with PVPS undergoing epididymectomy. Furthermore, Sweeney et al 22 reported a satisfaction level of 87.5% with this technique, recording best overall outcomes in the PVPS group, while Chen and Ball 23 indicated that 5 of 10 patients with PVPS (50%) were pain-free after epididymectomy. In spite of these successes, epididymectomy with PVPS remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the etiology of scrotal pain or epididymalgia remains unclear, mechanical obstruction with perineural fibrosis and epididymal compression from adjacent cysts have been postulated as possible etiologic factors in scrotal pain after vasectomy. 4,6 Postvasectomy changes of the epididymis were pathologically characterized by long-standing obstruction of the epididymal tubules. Tartar et al 7 attributed these changes to the backup of sperm into the epididymis with distention of the tubules leading to cystic change.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism in those without a history of vasectomy may be the same but the changes are not as marked (Chen & Ball, 1991). The work of Chen & Ball (1991) and Sweeney et al. (1998) demonstrated that the histological appearances are not good predictors of clinical outcome and therefore these are not commented upon in this study.…”
Section: Introductionmentioning
confidence: 91%